Rice calcium‐dependent protein kinase OsCPK17 targets plasma membrane intrinsic protein and sucrose‐phosphate synthase and is required for a proper cold stress response. (2nd March 2017) - Almadanim, M. Cecília; Alexandre, Bruno M.; Rosa, Margarida T.G.; Sapeta, Helena; Leitão, António E.; Ramalho, José C.; Lam, TuKiet T.; Negrão, Sónia; Abreu, Isabel A.; Oliveira, M. Margarida
Abstract: Calcium‐dependent protein kinases (CDPKs) are involved in plant tolerance mechanisms to abiotic stresses. Although CDPKs are recognized as key messengers in signal transduction, the specific role of most members of this family remains unknown. Here, we test the hypothesis that OsCPK17 plays a role in rice cold stress response by analysing OsCPK17 knockout, silencing and overexpressing rice lines under low temperature. Altered OsCPK17 gene expression compromises cold tolerance performance, without affecting the expression of key cold stress‐inducible genes. A comparative phosphoproteomic approach led to the identification of six potential in vivo OsCPK17 targets, which are associated with sugar and nitrogen metabolism, and with osmotic regulation. To test direct interaction, in vitro kinase assays were performed, showing that the sucrose‐phosphate synthase OsSPS4 and the aquaporin OsPIP2;1/OsPIP2;6 are phosphorylated by OsCPK17 in a calcium‐dependent manner. Altogether, our data indicates that OsCPK17 is required for a proper cold stress response in rice, likely affecting the activity of membrane channels and sugar metabolism. Abstract : Rice production is severely affected by different abiotic stresses, including cold. Cold perception is mediated by calcium signals that activate kinases to elicit the adequate cellular response. In this work, we show the involvement of the rice calcium‐dependent protein kinase 17 (OsCPK17) in such a process. We show that altered OsCPK17 gene expression in transgenic lines affects cold tolerance performance and that OsCPK17 targets proteins are associated with osmotic regulation, and sugar and nitrogen metabolism.